Life style profile of High School students and its association with Body Mass Index in Nagpur city, Central India - Hajare, Shilpa Trilok; Deoke, Aniruddha Ramdas; Saoji, Prachi Ajeet (Indian Journal of Community Health, 2016)
Background: In the present era with a drastic change in lifestyle of every individual, weight gain and obesity are posing a growing threat to health in countries all over the world. Once a problem of affluence, obesity growing in many developing countries also due to decreased physical activity, sedentary lifestyle, altered eating habits, increased fat content in diet and decreased social activities. It is therefore imperative that rising incidence of obesity is controlled by tracking the trend of obesity since childhood and by BCC activities. Aims & Objectives: To study the life-style profile of high school students and association of lifestyle with Body Mass Index. Material & Methods: A cross-sectional study was conducted in 565 high school students. Students were interviewed regarding daily activity, physical activity, hours of television and computer viewing and routine food habits. The anthropometric measurements were done. BMI was calculated according to WHO 2007 criteria. Results: The prevalence of overweight in students was found to be 5.84% and obesity was 0.35%. There was statistical evidence that the overweight students were associated with higher socio economic status group (p=0.000107), decreased physical activity (p= 0.0001; OR- 10.88), increased consumption of junk food (p=0.0005817; OR- 3.4) and more hours of viewing television/ computer (p=0.00555; OR- 2.99).